INTERACTIVE METHODS OF TEACHING ENGLISH LITERATURE - Jabaraliyeva Sevaraxon Nozimjonovna; Ibragimova Dilafruz Shukhratovna (TADQIQOTLAR.UZ, 2023)
Abstract: This article examines the problem of using methods of teaching literature in universities, to make it interesting and understandable for students. The idea that interactive teaching methods are a more convenient and effective way of teaching language and literature in a modern university is substantiated. The article also considers the topic of the teacher's activities performed by the students in a practical way using interactive teaching methods.